ANALISIS PENILAIAN PERSEDIAAN PADA PT. PUTRA WIRAWAN GAS KENDARI - Manaf, Abdul Manaf; Akib, Mulyati; Kusmiyati, Kusmiyati (JURNAL AKUNTANSI, 2016)
This study aimed to determine whether the inventory method applied toPT. Putra Wirawan Gas Kendari accordance with PSAK No. 14.Â  Inthepreparation of this paper, the authors chose the research object merchandiseinventory at PT. Putra Wirawan Gas Kendari.The method used in the valuation og inventory at PT. Putra Wirawan GasKendari is Deskriptive data analysis methods,namely the method of processingthe data by way of expalaining the method of inventory valuating made by thecompany with inventory valuating method in accordance with PSAK No. 14 in2012.The result of this study indicate that inventory valuation done PT. PutraWirawan Gas Kendari. Not in accordance with statement of financial AccountingStandars (SFAS) No. 14 because the company did not record the purchase costof goods (cost to transport) increase in value of inventories end represented lessthan the value that should be at the end the yearKeywords : Stock Estimastion